2 0 0 0 3 − 1 9 9 9 ⋅ 2 0 0 0 2 − 1 9 9 9 2 ⋅ 2 0 0 0 + 1 9 9 9 3 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good question!
Hey! FIRST i want to tell my english not good your solve is worng -1999^2* 2000 +1999^3 can't to -1999^2(2000-1999)
the right way it's must to -1999^2(2000+1999)
if im wrong im sorry
Log in to reply
You are wrong, as a negative has been factorized out ( − 1 9 9 9 2 ), all positives being factorized must now be negative, and all negatives go positive. My solution below uses a simpler method with no complication like this one. (even though this one is perfectly correct)
This is a nice way to solve this question! I took a long time to solve because I transformed all terms as 1999 and it's powers to solve it.
y = 2000 , x = 1999
The given expression = y^3 - x y^2 - y x^2 + x^3
= (y^3 - x y^2) - (y x^2 - x^3)
= y^2 (y - x) - x^2 (y - x) = (y - x)(y^2 - x^2) = (y - x)(y - x)(y + x)
= (1)(1)(3999) = 3999
Splendid.
Great job Gamal!
I said that x = 2000, then the equation becomes: = x 3 − ( x − 1 ) x 2 − ( x − 1 ) 2 x + ( x − 1 ) 3 = x 3 − ( x 3 − x 2 ) − ( x 3 − 2 x 2 + x ) + ( x 3 − 3 x 2 + 3 x − 1 ) = x 3 − x 3 + x 2 − x 3 + 2 x 2 − x + x 3 − 3 x 2 + 3 x − 1 = ( x 3 − x 3 ) + ( x 3 − x 3 ) + ( x 2 + 2 x 2 − 3 x 2 ) − x + 3 x − 1 = 2 x − 1 = 2 ⋅ 2 0 0 0 − 1 = 4 0 0 0 − 1 = 3 9 9 9
let 2000=x and 1999=y;
>x^3-yx^2-(y^2)x+y^3=x^2(x-y) -y^2(x-y) =(x-y)(x^2-y^2) =(x-y)(x-y)(x+y) =(2000-1999)(2000-1999)(2000+1999)=3999
200^3-1999(2000^2)-1999^2(2000)+1999^3
let 2000=x
we have;
x^3 - (x-1)(x^2) - (x-1)^2(x) + (x-1)^3
=X^3 - (x^3-x^2) - (x^3-2x^2+x) + (x^3-3x^2+3x-1)
=x^3 - x^3 + x^2 - x^3 + 2x^2 - x + x^3 -3x^2 + 3x-1
=(x^3 - x^3) + (x^2 + 2x^2 - 3x^2) + (-x^3 + x^3) ( -x + 3x ) - 1
=2x-1
substitute 2000 to x 2(2000)-1 =4000-1 =3999
Let k=1000; so 2000(^3)=2k^3. Equation becomes (2k)^3-(2k-1)(2k)^2-(2k-1)^2(2k)+(2k-1)^3. Multiply using algebra and combine like terms you end up with 4k-1 = 4000 -1= 3999. remember4k means the product of 4 and 1000 or4000.
A different approach since many math problems can be solved in different ways.
Steve, we think alike. Great job!
Problem Loading...
Note Loading...
Set Loading...
2 0 0 0 3 − 1 9 9 9 ⋅ 2 0 0 0 2 − 1 9 9 9 2 ⋅ 2 0 0 0 + 1 9 9 9 3
= 2 0 0 0 2 ( 2 0 0 0 − 1 9 9 9 ) − 1 9 9 9 2 ( 2 0 0 0 − 1 9 9 9 )
= 2 0 0 0 2 − 1 9 9 9 2
= ( 2 0 0 0 + 1 9 9 9 ) ( 2 0 0 0 − 1 9 9 9 )
= 3 9 9 9